2013
DOI: 10.1007/s12639-013-0411-5
|View full text |Cite
|
Sign up to set email alerts
|

High levels of urinary schistosomiasis among children in Bunuso, a rural community in Ghana: an urgent call for increased surveillance and control programs

Abstract: We investigated the occurrence of urinary schistosomiasis and estimated predictors for risk of infection among children in the Bunuso community of Ashanti Region of Ghana, West Africa. The cross-sectional survey was conducted between June and December 2009. Information was obtained on socio-demographic characteristics, schistosomiasis symptoms and other risk factors through interviews and questionnaires. Urine samples were analysed for Schistosoma haematobium ova using centrifugation and sedimentation, filtrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
(17 reference statements)
2
8
0
Order By: Relevance
“…However, comparison of some reported prevalence estimates for S. haematobium infection from some communities together with the present prevalence estimate, it is tempting to speculate that average prevalence rate of S. haematobium infection in Ghana may be high despite increasing national efforts in terms of education and mass treatment. Compared with S. haematobium infectionprevalence estimates from some studied communities in some African countries such as in Malawi (10.4 %), [26] Sudan (0.0 %), [27] Senegal, [28] and Kenya (9.3 %), [29] that of the present study is relatively high despite been lower compared to estimates from communities in Zimbabwe (68 %), [29] Nigeria (51-59.5 %), [31,32] and Benue state in Nigeria (41.5 %). [5] S. haematobium co-infection with S. mansoni and other soil-transmitted helminthes is reported elsewhere.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…However, comparison of some reported prevalence estimates for S. haematobium infection from some communities together with the present prevalence estimate, it is tempting to speculate that average prevalence rate of S. haematobium infection in Ghana may be high despite increasing national efforts in terms of education and mass treatment. Compared with S. haematobium infectionprevalence estimates from some studied communities in some African countries such as in Malawi (10.4 %), [26] Sudan (0.0 %), [27] Senegal, [28] and Kenya (9.3 %), [29] that of the present study is relatively high despite been lower compared to estimates from communities in Zimbabwe (68 %), [29] Nigeria (51-59.5 %), [31,32] and Benue state in Nigeria (41.5 %). [5] S. haematobium co-infection with S. mansoni and other soil-transmitted helminthes is reported elsewhere.…”
Section: Discussionmentioning
confidence: 91%
“…[26] Previous studies have shown that children from age 6-13 years are more at risk of S. haematobium infection while those above 13 years tend to have lower risk. [26] Unlike these reports, [26] it was observed that children aged between 16-19 years were more at risk of S. haematobium infection compared to younger children (< 15 years) (table 2) and this observation adds credence to an earlier report from Nigeria which showed that older children are more at risk than younger children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results is also in keeping with previous mass deworming, malarial prevention and schistosomiasis control exercises in this region [ 2 5 ]. Our data however suggest that despite the improved control efforts, there remain many inhabitants of riparian communities that suffer from urinary schistosomiasis [ 26 ]. Although we are not privy to the full repertoire of drugs admitted during these sessions, children had mostly been on praziquantel in various combinations with other drugs including antimalarial.…”
Section: Discussionmentioning
confidence: 99%